2020
DOI: 10.3390/horticulturae6020023
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in Propagation of Fruit, Vegetable and Ornamental Plants

Abstract: There are two primary forms of plant propagation: sexual and asexual. In nature, propagation of plants most often involves sexual reproduction, and this form is still used in several species. Over the years, horticulturists have developed asexual propagation methods that use vegetative plant parts. Innovation in plant propagation has supported breeding programs and allowed the production of high-quality nursery plants with the same genetic characteristics of the mother plant, and free of diseases or pests. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Plant propagation can be done sexually or asexually. In the process that occurs in nature, most plants reproduce sexually (Roberto 2020). In plant propagation, acclimation is one of the most important stages, because it is the stage when plants must adapt to a different growing environment from the usual environment.…”
Section: Discussionmentioning
confidence: 99%
“…Plant propagation can be done sexually or asexually. In the process that occurs in nature, most plants reproduce sexually (Roberto 2020). In plant propagation, acclimation is one of the most important stages, because it is the stage when plants must adapt to a different growing environment from the usual environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not check the monochromatic light combination for the PLB organogenesis of D. okinawense, and that may have the possibility for the further improvement of the PLB organogenesis. Previous studies also reported the efficiency of PLB organogenesis under the combination of the different monochromatic light [2,3,38]. Effectiveness of red and blue light is well known, while very few studies reported about the efficacy of the green light.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro micro-propagation is very common in orchid regenerations because of its complexity in vegetative and sexual propagations. Several in vitro techniques are followed for orchid micro-propagation, and propagation by PLB (protocorm-like-body) is one of them [1][2][3]. In vitro organogenesis of PLB was studied in different Dendrobium sp.…”
Section: Introductionmentioning
confidence: 99%
“…For example, experts recommend using the method of green cuttings for the same crop with the simultaneous use of other methods of reproduction. This increases the output of seedlings and contributes to the rational organization of labor in farms engaged in nursery [1,2,3].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the quality of the resulting planting material of grapes, it is necessary to ensure the invigoration of cuttings from viral diseases and other pathogens, as well as the use of a set of measures to stimulate plants to achieve the specified biometric indicators while they are in the field [1,4,5,6].…”
Section: Introductionmentioning
confidence: 99%